KEHALALAN MAKANAN CEPAT SAJI MENURUT FATWA MUI: STUDI ANALISIS TERHADAP RESTORAN CEPAT SAJI DI KOTA BOGOR - Irfan Helmi; Didin Hafidhuddin; Ibdalsyah Ibdalsyah (Univ Ibn Khaldun Bogor, 2019)
The results concluded that the criterias of fast food that is halal and which is haram in Islamic Shari'ah is determined by the presence or absence of unclean and unclean goods elements. MUI has arranged halal fast food products by establishing the System and Procedures for Stipulation of Fatwa Halal Products completely. LPPOM MUI has also set up MUI Halal Certification procedures in detail for fast-food restaurant products. National fast food restaurants in Bogor City have been certified halal MUI and have implemented Halal Assurance System (SJH). This is evidenced by the establishment of halal policy by Top Management; appointment of Halal Management Team; making HAS manual; implementation of Halal Assurance System training; preparation of HAS related procedures; internal audit implementation; and management review. The local fast food restaurants are generally not certified halal MUI, so it cannot be ascertained halal. Because to ensure it must go through an audit process that requires fast-food restaurant companies to register halal certification first. Therefore, the authors suggest that the government immediately implement the mandate of Halal Product Guarantee Act (JPH) by making the government regulation as derivative rule and complementing the working tool of the Halal Product Guarantee Organizer (BPJPH). In addition, fast-food restaurant entrepreneurs who have not been certified halal to immediately apply halal certification, in order to protect the interests of consumers of food products containing elements of illicit goods or impure. The people, especially the Muslims, are encouraged to consume halal certified halal food products, and be wary of processed food products that have not been certified halal, especially products that have a critical point on raw materials, additives, and auxiliary materials as well as on the production process.